Vanadium Catalyzed Partial Oxidation of Some Saturated Hydrocarbons to Functionalized Products Under Mild Conditions (Bangladesh Journal of Scientific and Industrial Research, 2008)
Partial oxidation of cyclopentane, cyclohexane, cycloheptane and propane to oxygenated products has been investigated using vanadyl acetylacetonate catalyst in presence of oxidant K2S2O8 in CF3COOH (TFA) solvent. It has been observed that the primary products were alcohols and carbonyl compounds. However, in the reaction of cycloheptane and propane, carbonyl was not formed. Alcohols subsequently reacted with TFAand produced esters. In case of propane, two esters were observed where iso-propyl trifluoroacetate was the dominant product and n-propyl trifluoroacetate was the minor product. In this case, about 89 mol% conversion was achieved. The conversion of cycloalkanes is found lower than that of propane. For the cyclohexane functionalization, the optimum condition found 7.5 mmol of K2S2O8, 5 mL of CF3COOH, 0.1 mmol of catalyst, 80Â°C reaction temperature and 1 mmol of cyclohexane.Â  Key words: Partial oxidation, Homogeneous catalysis, Hydrocarbon functionalization, Potassium persulfate and Trifluoroacetic acidDOI = 10.3329/bjsir.v43i3.1144Bangladesh J. Sci. Ind. Res. 43(3), 291-300, 2008